Media Authorship. - Chris, Cynthia (AFI film readers., 2013)
Contemporary media authorship is frequently collaborative, participatory, non-site specific, or quite simply goes unrecognized. In this volume, media and film scholars explore the theoretical debates around authorship, intention, and identity within the rapidly transforming and globalized culture industry of new media. Defining media broadly, across a range of creative artifacts and production cultures-from visual arts to videogames, from textiles to television-contributors consider authoring practices of artists, designers, do-it-yourselfers, media professionals, scholars, and others. Spec.